PENGARUH E-WOM, BRAND AWARENESS, DAN CUSTOMER EXPERIENCE TERHADAP KEPUASAN PELANGGAN DI MCDONALD’S MERR SURABAYA - Windelson; INDRAWATI, LILIK (Konsumen & Konsumsi : Jurnal Manajemen, 2025)
This study aims to analyze the influence of E-WOM, Brand Awareness, and Customer Experience on Customer Satisfaction at McDonald's MERR Surabaya. The method used in this research is a quantitative approach, where data is collected through questionnaires distributed to customers online via Google Forms. The data collected is processed using SPSS Version 30. The sampling technique used in this study is purposive sampling. The data analysis results indicate that all statements for all variables are valid, with calculated r-values > table r-values. The reliability test results conclude that all variables are reliable as the Cronbach's Alpha values are > 0.70. The normality test results show that the data used in this study follow a normal distribution. The multicollinearity test results indicate that there are no signs of multicollinearity. The heteroscedasticity test, based on scatterplot analysis, shows that there is no evidence of heteroscedasticity. The obtained multiple linear regression equation is Y = 5.081 + 0.028X1 + 0.175X2 + 0.211X3. The coefficient of determination test results show an adjusted R-square value of 0.432 or 43.2%. The t-test results indicate that the E-WOM variable (X1) has a calculated t-value of 0.418 < table t-value of 1.994 with a significance value of 0.677 > 0.05, meaning that E-WOM does not have an impact on customer satisfaction at McDonald's MERR Surabaya. The Brand Awareness variable (X2) has a calculated t-value of 1.910 < table t-value of 1.994 with a significance value of 0.060 > 0.05, indicating that Brand Awareness does not significantly affect customer satisfaction at McDonald's MERR Surabaya. The Customer Experience variable (X3) has a calculated t-value of 2.794 > table t-value of 1.994 with a significance value of 0.007 < 0.05, meaning that Customer Experience has a significant impact on customer satisfaction at McDonald's MERR Surabaya.